High-strength and high-definition light-transmittance nano glass ceramic with silicon yttrium lithium aluminate as well as preparation method and application of high-strength and high-definition light-transmittance nano glass ceramic

By introducing osmium oxide and zirconium oxide micropowder into the Li2O-Al2O3-SiO2 system glass and using the Li2O-Y2O3-Al2O3-SiO2 system process, high-intensity, high-definition, transparent nanocrystalline glass with lithium silicon yttrium aluminate was prepared, which solved the problem of insufficient hardness, toughness and light transmittance of existing glass materials and achieved the needs of a variety of high-end applications.

CN119591323APending Publication Date: 2025-03-11HUNAN JINGCI NEW MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411735579.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing Li2O-Al2O3-SiO2 system glass has problems such as blueness, concealment, fog, unclear vision, and insufficient fracture toughness and hardness.

Method used

Lithium oxide, yttrium oxide, alumina and silica of the Li2O-Y2O3-Al2O3-SiO2 system were used as raw materials, combined with zirconium oxide micropowder, and high-intensity high-definition transmissive nanocrystalline glass with lithium yttrium aluminate was prepared through melting and crystallization.

Benefits of technology

It achieves high strength, high definition light transmittance, high surface hardness, strong fracture toughness, good corrosion resistance, and light transmittance ≥90% and a small thermal expansion coefficient, making it suitable for a variety of high-end applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591323A_ABST
    Figure CN119591323A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of glass ceramics, and relates to high-strength high-definition light transmittance nano glass ceramics with silicon yttrium lithium aluminate as well as a preparation method and application of the high-strength high-definition light transmittance nano glass ceramics. The high-strength and high-definition light-transmittance nano glass ceramic containing silicon yttrium lithium aluminate is prepared from a synthetic aluminum-rich feldspar glass or ceramic glass material, and lithium oxide, yttrium oxide, aluminum oxide, silicon yttrium oxide and silicon yttrium lithium aluminate which are determined by Li2O-Y2O3-Al2O3-SiO2 system glass. The nanometer microcrystalline glass with silicon yttrium lithium aluminate is obtained by melting and crystallizing a raw material with silicon dioxide as a chemical component and zirconium oxide micro powder. The prepared nano microcrystalline glass is high in hardness and fracture toughness resistance, has high-definition light transmittance, and is suitable for manufacturing various optical glass, including mobile phone cover panels and back plates, high-end instrument and meter equipment window glass and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of microcrystalline glass, and relates to a high-strength, high-definition and light-transmitting nano-microcrystalline glass with lithium yttrium aluminate silicate, and a preparation method and application thereof. Background Art

[0002] As the application scope of display technology glass continues to expand, the performance requirements for display glass, including window glass, are becoming higher and higher, especially the requirements for display glass panel hardness, strength, fracture toughness, display clarity, light transmittance, corrosion resistance, etc. For example, as the cover or back cover glass of electronic devices such as 5G mobile phones, it must not only have good light transmittance of optical glass, that is, light transmittance ≥ 90%, but also have relatively high fracture toughness strength and high display clarity. The existing Li2O-Al2O3-SiO2 system glass has objective shortcomings, such as severe blueing of the glass, fogging, unclear vision, and low drop ball impact strength. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide a high-strength, high-definition, and light-transmitting nano-ceramic glass with lithium yttrium aluminate silicate (Li2O(Y2O3Al2O3)6SiO2) and its preparation method and application in view of the above-mentioned deficiencies of the glass materials in the prior art. The manufactured nano-ceramic glass has high mechanical strength, high display clarity and light transmittance, high surface hardness, high fracture toughness, good corrosion resistance, light transmittance ≥ 90%, and low thermal expansion coefficient; it can be widely used in the production of optical glass and window glass, including mobile phone cover panels or cover back panels, cover glass of high-end electronic products, high-speed trains, aircraft windshields and side window glass, high-end instrument and equipment window glass, etc.

[0004] The technical solution adopted to solve the technical problem of the present invention is:

[0005] One aspect of the present invention provides a high-strength, high-definition, and light-transmitting nano-microcrystalline glass having lithium yttrium aluminosilicate (Li2O(Y2O3Al2O3)6SiO2), which is obtained by melting and crystallizing raw materials including synthetic aluminum-rich feldspar glass or ceramic glass material, lithium oxide, yttrium oxide, aluminum oxide, and silicon dioxide determined by Li2O-Y2O3-Al2O3-SiO2 system glass, and zirconium oxide micropowder.

[0006] The lithium yttrium aluminosilicate (Li2O(Y2O3Al2O3)6SiO2) is a feldspar-like mineral with high strength, and its mechanical strength is greater than that of lithium aluminosilicate (i.e., lithium feldspar) mineral. In microcrystalline glass, lithium yttrium aluminosilicate can prevent the microcrystalline glass from being fogged and having no birefringence during the melting and crystallization process, thereby ensuring the optical transparency of the glass, which is beneficial for the production of optical glass lenses; lithium yttrium aluminosilicate can make the microcrystalline glass have good chemical stability, making the glass tough and scratch-resistant; lithium yttrium aluminosilicate-like feldspar can make the microcrystalline glass have the ability to absorb ultraviolet rays, which can protect the visual nerves; microcrystalline glass with lithium yttrium aluminosilicate can dissolve more nano ZrO2, which is more than twice that of Li2O Al2O3SiO2 system glass without the occurrence of ZrO2 opalescent glass phenomenon, which is beneficial for increasing the use of nano ZrO2 in (microcrystalline) glass, thereby improving the strength and fracture toughness (≥21MPam) of (microcrystalline) glass. 1 / 2 ).

[0007] Preferably, the chemical formula of the synthetic aluminum-rich feldspar glass or ceramic glass material is K2O / Na2O / Li2O / CaO / BaOXAl2O3YSiO2, 1.1≤X≤2.4, Y=2-6, which is represented by a glass or composite ceramic glass material of one or two or more of synthetic aluminum-rich potassium feldspar, synthetic aluminum-rich sodium feldspar, synthetic aluminum-rich sodium potassium feldspar, synthetic aluminum-rich lithium feldspar, synthetic aluminum-rich calcium feldspar, and synthetic aluminum-rich barium feldspar,

[0008] Among them, the two or more kinds of synthetic aluminum-rich feldspar glass or composite ceramic glass materials at least include synthetic aluminum-rich sodium feldspar glass or composite ceramic glass material.

[0009] Preferably, the raw materials for melting high-strength, high-definition, and light-transmitting nano-ceramic glass with lithium yttrium aluminate silicate include, by weight percentage:

[0010] The synthetic aluminum-rich feldspar glass or ceramic glass material is 1%-30%,

[0011] The Li2O-Y2O3-Al2O3-SiO2 system glass contains 65% to 90% of the raw materials of lithium oxide, yttrium oxide, aluminum oxide and silicon dioxide as chemical components.

[0012] The zirconium oxide powder is 2.5%-12%,

[0013] Nucleating agent 1%-5%,

[0014] Clarifying agent 0.5%-3%,

[0015] Also includes gallium oxide 0%-5%,

[0016] Obtain batch materials for molten glass.

[0017] Preferably, the raw materials of the Li2O-Y2O3-Al2O3-SiO2 system glass, which are determined as lithium oxide, yttrium oxide, aluminum oxide and silicon dioxide, include the following chemical components in weight percentage: Li2O 10%-16%, Y2O3 2%-20%, Al2O3 0.5%-8%, SiO2 68%-86.5%, SnO2 1.0%-3% as a clarifier, and P2O5 1%-5% as a crystal nucleating agent.

[0018] It is further preferred that the synthetic aluminum-rich feldspar glass or ceramic glass material is a synthetic aluminum-rich sodium-potassium feldspar glass or ceramic glass material, the chemical components contained therein include by weight percentage: Na2O 8%-12%, K2O 1%-3%, Al2O3 20%-30%, SiO2 50%-60%, CaO 3%-7%, MgO 1%-3%, ZrO2 0.5%-5%, Sb2O3 0.03%-0.3%, La2O3 0.3%-5%.

[0019] It is further preferred that the Y2O3 and the ZrO2 are synthesized into a yttria-stabilized zirconia solid solution during the melting process, the particle size of the yttria raw material is less than 100nm, and the other raw materials are powder materials with a particle size of 1000-2000 mesh, and the obtained nano-crystal glass with lithium yttrium aluminate silicate is obtained. The principle of solid chemical reaction reveals that the particle size of the solid phase is the key issue in determining the uniform speed of the solid phase reaction. Therefore, the powder material used in the present invention should be controlled at 1000-2000 mesh, yttria is within 100nm, and the formula organization material ingredients are subjected to pollution-free ball milling (small particle ball milling medium Φ1-2mm accounts for more than 60%), and the ball milling uniform solid phase material is used as the precursor material (D5090%) of the glass material of this technology.

[0020] Preferably, the raw material formula of the nano-crystal glass with lithium yttrium aluminosilicate includes SnO2, which is used as a solubility agent for synthesizing nano Y2O3 and ZrO2 into yttria-stabilized zirconia solid solution during the melting and crystallization process, so that the weight percentage of ZrO2 dissolved in Y2O3 in the nano-crystal glass is in the range of 0.5%-12% to synthesize yttria-stabilized zirconia solid solution nano-crystals without producing milky white crystals. Up to 12% zirconium oxide in the raw material can greatly increase the strength of the nano-crystal glass of the present invention (zirconia is a high-hardness material and has a toughening effect), and improve the toughness of the nano-crystal glass. In general glass, when the zirconium oxide content exceeds 5%, the glass is easily emulsified and whitened, becoming milky white glass. Nano Y2O3 dissolves nano ZrO2 to synthesize nano yttria-stabilized zirconium oxide solid solution. When SnO2 is present in the raw material formula and the amount of SnO2 is within the scope of the clarifier, nano Y2O3 can dissolve nano ZrO2 up to 12% by weight without making the glass whitish (not turning into opalescent glass), which is beneficial to improving the strength and toughness of the glass. In the Li2O-Y2O3-Al2O3-SiO2 system glass composed of yttria, yttria itself has a stable solid solution with nano ZrO2, which completely prevents the extinction factor of the glass from turning yellow and red (brown red) and reducing the clear transmittance. At the same time, the presence of SnO2 in the raw material formula makes the saturated amount of nano Y2O3 dissolving nano ZrO2 in the glass reach 12% by weight, eliminating the large amount of ZrO2 existing in the network body to reduce the transmittance.

[0021] It is further preferred that the nanocrystalline phases precipitated in the nano-crystalline glass include, by volume percentage: 1%-30% sodium nepheline, 20%-50% lithium yttrium aluminate feldspar, 30%-50% lithium disilicate crystals (Li2O·2SiO2), 3%-15% yttrium aluminum garnet, 1%-5% spodumene, and the nanocrystals account for 90%-95% of the total nano-crystalline glass with lithium yttrium aluminate.

[0022] It is further preferred that the nanocrystals in the nano-ceramic glass are nanocrystals with grains smaller than 50 nm.

[0023] It is further preferred that the chemical composition of the basic glass after nano-crystal crystallization is as follows:

[0024] Al2O32%-3.7%, Y2O32%-10%, Li2O 10%-16%, Na2O 1%-2%, K2O 0.2%-0.6%, SnO 0.5%-3%, Sb2O30.3%-0.5%, SiO258.9%-82.3%, La2O30.1%-2%ZrO2

[0025] 2.5%-12%, P2O51%-5%, Ga2O30%-5%. Gallium oxide in the glass network strengthens the glass network structure and helps to improve the puncture resistance of the glass.

[0026] The second aspect of the present invention provides a method for preparing high-strength, high-definition and light-transmittance nano-ceramic glass having lithium yttrium aluminate silicate, comprising:

[0027] Preparation of synthetic raw materials: The synthetic raw materials in the high-strength, high-definition and light-transmitting nano-ceramic glass with lithium yttrium aluminate silicate are synthesized according to a ratio to obtain the corresponding synthetic mineral material;

[0028] Formula batching: Compound the synthetic material with other raw materials according to the formula ratio requirements;

[0029] Processing and mixing: crush the raw materials of the ingredients to the required fineness, mix and mix evenly to obtain dry powder glass raw batch;

[0030] Melting molding: Add the dry powder batch into the glass melting equipment for melting, clarification and homogenization, and use appropriate molding methods according to product requirements;

[0031] Nucleation and crystallization: The formed glass products are nucleated at the nucleation temperature, and then crystallized by controlling the temperature and time to control the grain growth into microcrystals or nanocrystals of the required fineness and microcrystal quantity;

[0032] Annealing: Anneal the crystallized product to eliminate the thermal stress in the glass body to obtain high-strength, high-definition and light-transmitting nano-ceramic glass products.

[0033] Preferably, the method for preparing the high-strength, high-definition and light-transmitting nano-ceramic glass with lithium yttrium aluminosilicate further comprises: further molding and processing the nano-ceramic glass product to obtain the desired structure, and then performing a strengthening treatment.

[0034] It is further preferred that the strengthening of the nano-crystalline glass product includes physical strengthening or chemical strengthening.

[0035] It is further preferred that the chemical strengthening is one-time chemical strengthening or two-time chemical strengthening, and the depth of the surface compressive stress layer generated by ion exchange of the nano-ceramic glass product after strengthening is 60 μm-200 μm.

[0036] It is further preferred that the two chemical strengthenings are two step ion exchange strengthenings, wherein the first strengthening is Na + →Li + (Sodium ions replace lithium ions), the second strengthening is K + →Na + (potassium ions replace sodium ions), K +→Li + (Potassium ions replace lithium ions), thereby greatly improving the mechanical strength of the glass microcrystals.

[0037] It is further preferred that in the two step ion exchange enhancements:

[0038] The first strengthening step is to place the nano-ceramic glass product in molten salt, wherein the molten salt is: KNO3 95wt% + NaNO3 4.8wt%-5wt% + CsNO3 0-0.2wt% plus 0.5wt% Al2O3 powder, at 460°C-480°C, and keep the temperature for 4-6 hours;

[0039] The second strengthening is as follows: the nano-ceramic glass product after the first strengthening is placed in molten salt again, the molten salt used is KNO3, and the temperature is kept at 380℃ KNO3 molten salt for 2-6 hours.

[0040] Preferably, the dry powder batch material is added to the glass melting equipment in the melting molding, that is, the dry powder batch material is added to the sagger for melting glass, and the sagger is placed in a high-temperature furnace in an oxidizing atmosphere or an oxidizing-reducing atmosphere for melting, clarifying and homogenizing.

[0041] It is further preferred that the sagger is a magnesium aluminum spinel sagger or an α-corundum-mullite sagger or an α-corundum-quartz glass sagger.

[0042] Further preferably, the magnesia-alumina-spinel sagger is a synthetic composite magnesia-alumina-spinel sagger.

[0043] Preferably, the nucleation crystallization adopts an in-situ growth method, that is, the glass is formed directly by in-situ shaping of the sagger, and the sagger together with the glass in the sagger is directly nucleated and crystallized in a kiln and then annealed to obtain high-definition and light-transmitting nano-ceramic glass.

[0044] It is further preferred that the high-definition and light-transmitting nano-ceramic glass obtained by the in-situ growth nucleation and crystallization is separated from the sagger, and further formed and processed to obtain the required structural parts, and then strengthened.

[0045] Preferably, in the melt-molding, the dry powder batch material is added into a glass melting furnace for melting, clarification and homogenization, and the molding is performed by casting, calendering or overflow molding.

[0046] More preferably, the melting temperature is 1550°C to 1600°C, the clarifying temperature is 1580°C to 1600°C, and the molding temperature is 1350°C to 1410°C.

[0047] Preferably, the nucleation crystallization is performed on the formed product, and the temperature of the nucleation crystallization is: nucleation at a temperature of 530°C-580°C, nucleation time: 2-4h, crystallization temperature 600°C-650°C, crystallization time: 2-4h.

[0048] Preferably, the annealing temperature is: the crystallized product is heated from room temperature to 500°C-550°C, the heating rate is 0.5°C-1°C / min, the annealing holding time is 2-4 hours, and the cooling rate from the annealing holding temperature to room temperature is 0.2°C-0.4°C / min.

[0049] Preferably, before the nucleation and crystallization, the formed glass product is pre-annealed, and the process is: first, the glass product is raised from the temperature after molding to 650°C-750°C, and the heat preservation time is 2-5h, and then the temperature is reduced to 530°C-580°C at 0.2°C-0.3°C / min for the pre-annealing, and the pre-annealing heat preservation time is 2-3 hours, and then the temperature is reduced to 500°C at 0.2°C-0.3°C / min, and the heat preservation time is 2-3 hours, and then the temperature is raised to the nucleation temperature at no more than 0.5°C / min, and the subsequent nucleation, crystallization and annealing are carried out.

[0050] The third aspect of the present invention provides an application of a high-strength, high-definition, and light-transmitting nano-microcrystalline glass with lithium yttrium aluminosilicate. The high-strength, high-definition, and light-transmitting nano-microcrystalline glass with lithium yttrium aluminosilicate is used to make various optical glasses, including mobile phone cover panels and cover back panels, cameras (high-definition and light-transmitting, non-fogging camera lenses), cover glass for high-end electronic products, and high-speed trains, aircraft windshields and side window glass, high-end instrumentation equipment window glass, vehicle-mounted control screens, quantum radar panels, etc.

[0051] The high-strength and high-transmittance nano-crystal glass of the present invention replaces most or all of the Al2O3 in the Li2O-Al2O3-SiO2 system glass with high-strength material yttrium oxide (Y2O3), because the hardness of the Y2O3 material is comparable to that of sapphire, and the fracture toughness is comparable to that of ZrO2 (cubic) porcelain. Therefore, the strength performance of the Li2O-Y2O3-Al2O3-SiO2 system basic glass is definitely much better than that of the Li2O-Al2O3-SiO2 system glass due to the presence of Y2O3, and the microcrystals are dominated by lithium yttrium aluminate silicon microcrystals, so that the nano-crystal glass of the present invention is not yellow, blue, or foggy, has high-definition transmittance, and has a transmittance of 91%-96%, and has small grains, small expansion coefficient, high thermal stability, high strength, high toughness, and sandpaper drop height performance test: the standard 80-mesh sandpaper puncture strength is ≥100cm, meeting the requirements of increasingly advanced electronic products.

[0052] The high-strength and high-transmittance nano-ceramic glass of the present invention meets the following technical performance indicators: Drop height test: a glass sheet with a length and width of 5X 5cm and a thickness of 0.5mm falls vertically from a height of 2.5 meters without breaking, fracture toughness: 10-15MPam before strengthening 1 / 2 , after strengthening 16-22MPam 1 / 2 , Hardness: Mohs hardness before strengthening 6-8 Mohs hardness after strengthening 8-9, Optical properties: 1. Refractive index: 1.56-1.6; 2. 91% ≤ visible light transmittance <96%; 3. Haze: <0.1%, blue value B<0.1, with good high-definition transmittance. Mechanical properties include: 1. Poisson's ratio: 0.21~0.23; 2. Young's modulus after strengthening: 11.5~14.1Mpsi; 3. Vickers hardness before strengthening ≥660kgf / mm 2 , Vickers hardness after strengthening ≥780kgf / mm 2 ; 4. The bending strength before strengthening is ≥600Mpa, the bending strength after strengthening is greater than 800Mpa, and the ring-on-ring strength is 3200Mpa-5000Mpa after strengthening (glass plate thickness 0.4-0.6mm). Ball drop performance: ball drop degree ≥60cm; sandpaper drop height performance: standard 80-mesh sandpaper puncture strength ≥100cm (i.e. sandpaper drop height ≥100cm, the existing Li2O-Al2O3-SiO2 system glass standard sandpaper puncture strength fluctuates in the range of 30-100cm, and it is difficult to stabilize at ≥100cm, which affects the promotion and use of the glass. That is, nano-scale (nm) Y2O3 yttrium oxide is used to strengthen the network structure in the Li2O-Y2O3-Al2O3-SiO2 system glass, and nano-crystals are precipitated from the matrix glass of this system. And the glass structure of the network body with intersecting frames of bridging oxygen polyhedron vertices is used to improve the drop ball impact strength of the Li2O-Al2O3-SiO2 system glass to form the advantage of filling and complementing)

[0053] The reasons for the high clarity and light transmittance of the nano-crystal glass of the present invention are as follows: 1. The yttrium oxide (Y2O3) material not only has the hardness of sapphire and white sapphire, but also the nano-crystals Li2O-Y2O3﹒Al2O3-6SiO2 precipitated from the Li2O-Y2O3-Al2O3-SiO2 of the present invention have both low expansion coefficients and make the crystals (crystals) and the mother glass have very close refractive indices (1.56-1.6), resulting in good transparency of the composite material. At the same time, part of the yttrium oxide (Y2O3) forms a solid solution with aluminum oxide (Al2O3), resulting in very close refractive indices (no birefringence). 2. The solid solution of Y2O3﹒Al2O3 material induces Li2O-Y2O3﹒ The crystallization behavior of Al2O3-6SiO2 glass itself (temperature-sensitive phenomenon: when kept at 600℃-700℃, nano-crystal nuclei will develop into nano-crystals of ≤100nm)) is such that even if there is more than 4% ZrO2, part of the yttrium oxide dissolves the ZrO2 (including ZrO2 introduced from synthetic alumina-rich feldspar glass or ceramic glass materials and separately added nano-zirconia powder) to synthesize a stable solid solution nucleation agent, and in the presence of SnO2, the ability of yttrium oxide to dissolve ZrO2 is greatly improved (up to 12% of the total glass amount), and there is no free ZrO2. This avoids the problem that the Li2O-Al2O3-SiO2 glass is easily "hazy" in the crystallization temperature zone (coarse crystals cause the clarity of the glass to drop sharply. Examples have shown that it is difficult to solve the "hazy" and unclear phenomenon even if "Li2O-Al2O3-SiO2 glass" only adopts a semi-crystallization system (the glass crystallinity is less than 50%). 3. When the "Li2O-Al2O3-SiO2" system glass crystallizes, it not only becomes hazy but also turns blue, resulting in a B value ≥ 0.5. The Li2O-Y2O3-Al2O3-SiO2 system glass of the present invention completely solves this shortcoming, and the transparency and clarity are naturally improved.

[0054] The role of nano-yttrium oxide in the glass of the present invention: 1. Significantly improve the thermal stability of the glass: nano-Y2O3+Al2O3→Y3Al5O 12 (Yttrium aluminum garnet is formed by sintering at 1550℃), Yttrium aluminum garnet Y3Al5O 121. It has a low coefficient of thermal expansion and improves the thermal stability of glass; 2. It improves the mechanical strength, hardness, wear resistance and impact strength of glass. It is not only suitable for high-strength and wear-resistant electronic screen glass, but also more suitable for bulletproof military protective glass. 3. It improves optical performance, reduces refractive index and defocus (improves focusing performance), so that optical glass has better imaging quality and high transmittance. 4. Radiation resistance: high absorption of radiation; 5. Nano-yttrium oxide and nano-ZrO2 form a solid solution, which can fully precipitate nano-crystals within the temperature of the glass crystallization zone, and can also prevent lithium-rich silicon (Li2O in the Li2O-Y2O3-Al2O3-SiO2 system that exceeds the molar ratio of lithium yttrium aluminate Li2O (Y2O3Al2O3) 6SiO2) glass crystals from growing into micron crystals.

[0055] Part (about 1 / 5) nano Y2O3+Al2O3→Y3Al5O 12 (yttrium aluminum garnet), the rest of the nano Y2O3 + nano ZrO2 → Y2O3XZrO2 (yttria stabilized zirconium oxide solid solution, X is the mole number of ZrO2) nucleating agent, the present invention adopts SnO2 as a clarifier, in the presence of SnO2, Y2O3 makes the glass non-blue and non-fog, that is, the spodumene nano-crystals in the nano-nano-crystal glass are not foggy in the glass, and Y2O3 stabilizes ZrO2 in the glass to dissolve more ZrO2, which can reach 12wt%, forming a solid solution of yttria stabilized zirconium oxide so that the glass is not whitish (will not become milky white glass), yttria stabilized zirconium oxide solid solution can control the crystallization speed of nano-crystal glass microcrystals, and does not form micron-level crystals in the crystallization zone. The electronegativity of yttrium is smaller than that of aluminum in Al2O3, and the ability to be oxidized to form bridging oxygen bonds is strong, which is conducive to the transparency of the glass, is conducive to controlling crystal growth, is conducive to the repair of glass bridging oxygen bonds, and improves strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 Example 1 of the present invention Table 1 Preparation Example 6 Scanning electron microscope (SEM) image of the microstructure of nano-nano-ceramic glass magnified 200K times.

[0057] Figure 2 Nano-nano glass-ceramic Example 1 Table 1 X-ray diffraction pattern of Preparation Example 6. DETAILED DESCRIPTION

[0058] To further illustrate the technical means and effects of the present invention, the following is a detailed description in conjunction with the preferred embodiments of the present invention and the accompanying drawings.

[0059] The technical solutions in the embodiments of the present application will be described clearly and completely below in combination with the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.

[0060] In the description of the present application, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more features. In the description of the present application, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0061] In this application, the word "exemplary" is used to mean "used as an example, illustration, or description." Any embodiment described in this application as "exemplary" is not necessarily to be construed as being preferred or advantageous over other embodiments. The following description is given to enable any technician in the field to implement and use the present application. In the following description, details are listed for the purpose of explanation. It should be understood that a person of ordinary skill in the art can recognize that the present application can be implemented without using these specific details. In other instances, well-known structures and processes will not be elaborated in detail to avoid obscuring the description of the present application with unnecessary details. Therefore, the present application is not intended to be limited to the embodiments shown, but is consistent with the widest scope consistent with the principles and features disclosed in the present application.

[0062] In order to obtain nano-crystal glass with high strength, high clarity and high chemical stability, a high-strength matrix glass system must be selected first. The present invention uses nano-level (nm) yttrium oxide Y2O3 to strengthen the network structure in the Li2O-Y2O3-Al2O3-SiO2 system glass, and simultaneously uses aluminum-rich Al2O3 feldspar mineral raw materials to form a matrix glass system. Y2O3Al2O3 and aluminum-rich feldspar minerals melted at 1500℃-1620℃ form a matrix glass that is transparent. Nano-crystals are precipitated from the matrix glass of this system, and the glass has high strength and hardness, mainly because the aluminum-rich Al2O3 content and yttrium oxide Y2O3 in the feldspar strengthen the network structure in the Li2O-Y2O3-Al2O3-SiO2 system glass. Nano-crystal glass is a hard, dense and uniform multi-phase material composed of crystal phase and glass, which is made by microcrystallization on the basis of matrix glass, and is also called ceramic glass. The present invention uses feldspar matrix glass raw material as a hard template material for crystallization, and further increases the amount of Al2O3 to improve the glass strength. In order to make the nano-ceramic glass transparent, the crystallite size is smaller than the wavelength of visible light (360nm-950nm), even if the crystallite size reaches the nanometer level, and in order to achieve a higher level of transmittance such as visible light transmittance> 90% or more, the crystallite size is controlled to be within the range of 100 nanometers (30-50 nanometers), and the refractive index of the glass matrix, nano-crystals and solid solution is basically close to unity, and in order to obtain high strength, the crystallite amount is 90-95% (vol%). The nano-ceramic glass obtained in this way is a nano-ceramic glass with high strength, high hardness and high clarity.

[0063] The following are non-limiting examples of the present invention:

[0064] Example 1

[0065] A high-strength, high-definition, and light-transmitting nano-microcrystalline glass with lithium yttrium aluminate is obtained by melting and crystallizing raw materials including synthetic alumina-rich feldspar glass or ceramic glass material, lithium oxide, yttrium oxide, aluminum oxide, and silicon dioxide determined by Li2O-Y2O3-Al2O3-SiO2 system glass, and zirconium oxide micropowder. The raw materials for melting the high-strength, high-definition, and light-transmitting nano-microcrystalline glass with lithium yttrium aluminate include, by weight percentage:

[0066] The synthetic aluminum-rich feldspar glass or ceramic glass material is 1%-30%,

[0067] The Li2O-Y2O3-Al2O3-SiO2 system glass contains 65% to 90% of the raw materials of lithium oxide, yttrium oxide, aluminum oxide and silicon dioxide as chemical components.

[0068] The zirconium oxide powder is 2.5%-12%,

[0069] Nucleating agent 1%-5%,

[0070] Also includes gallium oxide 0%-5%,

[0071] Clarifying agent 0.5%-3%,

[0072] Obtain batch materials for molten glass.

[0073] The chemical formula of the synthetic aluminum-rich feldspar glass or ceramic glass material is K2O / Na2O / Li2O / CaO / BaOXAl2O3YSiO2, 1.1≤X≤2.4, Y=2-6, which is represented by one or two or more synthetic aluminum-rich feldspar glass or composite ceramic glass materials selected from the group consisting of synthetic aluminum-rich potassium feldspar, synthetic aluminum-rich sodium feldspar, synthetic aluminum-rich sodium potassium feldspar, synthetic aluminum-rich lithium feldspar, synthetic aluminum-rich calcium feldspar, and synthetic aluminum-rich barium feldspar, wherein the two or more synthetic aluminum-rich feldspar glass or composite ceramic glass materials include at least synthetic aluminum-rich sodium feldspar glass or composite ceramic glass material. The synthetic alumina-rich feldspar ceramic glass material is prepared according to the chemical formula K2O / Na2O / Li2O / CaO / BaOXAl2O3YSiO2, in which the weight percentages of K2O / Na2O / Li2O / CaO / BaO, Al2O3, and SiO2 are proportioned. The corresponding precursor raw materials containing K2O / Na2O / Li2O / CaO / BaO, Al2O3, and SiO2 are prepared into a batch material, which is then ground through a 300-1000 mesh sieve. The obtained dry powder is sintered at a firing temperature of 1200°C-1300°C to obtain a thermally synthesized ceramic glass material, or the obtained dry powder is melted at a melting temperature of 1400°C-1500°C and then water quenched to obtain a synthetic alumina-rich feldspar glass material.

[0074] Preferably, the synthetic aluminum-rich feldspar glass or ceramic glass material is a synthetic aluminum-rich sodium-potassium feldspar (Na2OK2OXAl2O3YSiO2, X=2.3, Y=6 synthetic aluminum-rich sodium-potassium feldspar) glass or ceramic glass material, wherein the chemical components contained therein include by weight percentage: Na2O 8%-12%, K2O 1%-3%, Al2O3 20%-30%, SiO2 50%-60%, CaO 3%-7%, MgO 1%-3%, ZrO2 0.5%-5%, Sb2O3 0.03%-0.3%, La2O3 0.3%-5%.

[0075] Preferably, the raw materials of the Li2O-Y2O3-Al2O3-SiO2 system glass, which are chemically composed of lithium oxide, yttrium oxide, aluminum oxide and silicon dioxide, include the following chemical components in weight percentage: Li2O 10%-16%, Y2O3 2%-20%, Al2O3 0.5%-8%, SiO2 68%-86.5%, and also include gallium oxide 0%-5%, SnO2 1.0%-3% as a clarifier, and P2O5 1%-5% as a crystal nucleating agent.

[0076] It is further preferred that the chemical components contained in the synthetic aluminum-rich sodium potassium feldspar glass or ceramic glass material include, by weight percentage: Na2O 10%, K2O 2%, Al2O3 25%, SiO2 54.4%, CaO 5.3%, MgO 2%, ZrO2 0.5%, Sb2O3 0.3%, La2O3 0.5%.

[0077] The raw materials of the Li2O-Y2O3-Al2O3-SiO2 system glass, which are lithium oxide, yttrium oxide, aluminum oxide and silicon dioxide as chemical components, include the following chemical components in weight percentage: Li2O 10%-16%, Y2O3 2%-20%, Al2O3 0.5%-8%, SiO2 68%-86.5%, and also include Ga2O3 0%-5%, and SnO2 1.0%-3% is added as a clarifier and P2O5 1%-5% as a crystal nucleating agent. Therefore, when the determined synthetic aluminum-rich sodium potassium feldspar (Na2OK2OXAl2O3YSiO2, X=2.3, Y=6 synthetic aluminum-rich sodium potassium feldspar) glass or ceramic glass material is used and the raw materials with lithium oxide, yttrium oxide, aluminum oxide, and silicon dioxide as chemical components determined by the Li2O-Y2O3-Al2O3-SiO2 system glass, and the raw materials determined by Ga2O3 and P2O5 components are taken according to weight percentage, the weight percentage (Wt%) ratio of the raw materials of Li2O, Y2O3, Al2O3, SiO2, Ga2O3, SnO2, and P2O5 chemical components required in the formulations of each preparation example in this embodiment is obtained, as shown in Table 1 below.

[0078] It should be noted that in Table 1: the synthetic aluminum-rich feldspar glass or ceramic glass material is only the preparation examples (a total of 12 preparation examples) obtained by mixing the synthetic aluminum-rich sodium-potassium feldspar (Na2O K2O XAl2O3YSiO2, X=2.3, Y=6 synthetic aluminum-rich sodium-potassium feldspar) glass or ceramic glass material with the raw materials of lithium oxide, yttrium oxide, aluminum oxide and silicon dioxide as the chemical components determined by the Li2O-Y2O3-Al2O3-SiO2 system glass in a weight percentage within the ratio range. Therefore, the synthetic aluminum-rich feldspar glass or ceramic glass material can be one or two or more of the following synthetic aluminum-rich potassium feldspar, synthetic aluminum-rich sodium feldspar, synthetic aluminum-rich sodium potassium feldspar, synthetic aluminum-rich lithium feldspar, synthetic aluminum-rich calcium feldspar, and synthetic aluminum-rich barium feldspar as needed. A large number of preparation examples of the desired performance can be obtained by taking different values ​​of weight percentage within the ratio range of the raw materials with the chemical components of lithium oxide, yttrium oxide, aluminum oxide, and silicon dioxide determined by the Li2O-Y2O3-Al2O3-SiO2 system glass and the raw materials containing the chemical components of Ga2O3, SnO2, and P2O5. They will not be described here one by one.

[0079] The total amount of ZrO2 in the synthetic alumina-rich feldspar glass or ceramic glass material, which is in the range of 0.5%-5%, and the directly added nano zirconium oxide powder, which is in the range of 4%-12%, is mainly controlled by Y2O3 (in the presence of SnO2, the amount of yttria dissolving and stabilizing zirconium oxide can reach 12% of the total amount of nano-crystal glass without the appearance of opacity and whitening, so that the nano-crystal glass can still maintain high clarity and transmittance). Nano-yttria Y2O3 is used as a stabilizer for zirconium oxide ultrafine powder. The amount used is zirconium oxide: yttria = 90-95: 5-10 to generate a solid solution of yttria-stabilized zirconium oxide. According to performance requirements, the proportion of ZrO2 in nano-crystal glass can be increased within the range of 0.5%-12% to effectively improve the strength of nano-crystal glass. Nano-Y2O3 simultaneously synthesizes Y2O3 Al2O3 solid solution in Li2O-Y2O3-Al2O3-SiO2 system glass to generate yttrium aluminum garnet (Y3Al5O 12 ). The content range of yttrium oxide is determined from the above two aspects.

[0080] A part of the Y2O3 raw material and the ZrO2 component contained in the synthetic aluminum-rich sodium potassium feldspar glass or ceramic glass material are synthesized into yttria-stabilized zirconium oxide solid solution as a nucleating agent during the melting process. The particle size of the yttria raw material is less than 100nm, and the other raw materials are powder materials with a particle size of 1000-2000 mesh. The obtained microcrystalline glass with lithium yttrium aluminate silicate is a nano-microcrystalline glass. Therefore, the powder material used in the present invention is controlled at 1000-2000 mesh, yttria is within 100nm, and the formula organization material ingredients are subjected to pollution-free ball milling (small particle ball milling medium Φ1-2mm accounts for more than 60%), and the ball milling uniform solid phase material is used as the precursor material (D5090%) of the glass material of this technology.

[0081] Preferably, the raw material formula of the lithium yttrium aluminate silicate nano-crystal glass includes SnO2, which is used as a solvent for synthesizing nano Y2O3 and ZrO2 into yttria-stabilized zirconia solid solution during the melting process, so that the weight percentage of ZrO2 that can dissolve Y2O3 in the nano-crystal glass of the present invention is in the range of 0.5-16% to synthesize into yttria-stabilized zirconia solid solution nano-crystals without producing milky white crystals. Up to 12% zirconium oxide in the raw material can greatly increase the strength of the nano-crystal glass of the present invention (zirconia is a high-hardness material). In general glass, when the zirconium oxide content exceeds 5%, the glass is easily emulsified and whitened, becoming milky white glass. Nano Y2O3 dissolves nano ZrO2 to synthesize nano yttria-stabilized zirconia solid solution. When SnO2 exists in the raw material formula and the amount of SnO2 is within the use range of the clarifier, it becomes a solvent to make nano Y2O3 soluble in nano ZrO2 up to 12% by weight without making the glass white (it will not become opalescent glass), maintaining the high clarity and transmittance of the nano-glass-ceramics without being affected, and is beneficial to improving the strength of the glass. In the Li2O-Y2O3-Al2O3-SiO2 system glass composed of yttrium oxide, nano yttrium oxide itself has the ability to form a stable solid solution with the ZrO2 component contained in the synthetic aluminum-rich sodium potassium feldspar glass or ceramic glass material, thereby preventing the glass from turning yellow or red (brown-red) and the extinction factor from reducing the clarity and transmittance of the glass. At the same time, the presence of SnO2 in the raw material formula enables the saturated amount of nano Y2O3 dissolved in the glass to reach 12% by weight to form a stable solid solution, thereby eliminating the large amount of ZrO2 present outside the network that reduces the transmittance.

[0082] The glass batch is melted into a shape and then subjected to nucleation and crystallization to obtain the high-strength, high-definition and light-transmitting nano-crystal glass with lithium yttrium aluminate. The nano-crystal phases precipitated in the nano-crystal glass include, by volume percentage, 1%-30% of sodium nepheline, 20%-50% of lithium yttrium aluminate feldspar, 30%-50% of lithium disilicate crystals, 3%-15% of yttrium aluminum garnet, and 1%-5% of spodumene, wherein: the lithium yttrium aluminate feldspar crystals are composed of part of lithium disilicate crystals (Li2Si2O7) and part of yttrium aluminum garnet (Y3Al5O 12 ) synthesized lithium yttrium aluminate silicate (LiYAl(SiO3)) feldspar. The total amount of nanocrystals accounts for 90%-95% of nanocrystal glass.

[0083]

[0084]

[0085]

[0086]

[0087]

[0088]

[0089]

[0090] The nano-crystalline glass obtained as described above is a high-strength, high-definition and light-transmitting nano-crystalline glass with lithium yttrium aluminosilicate.

[0091] Preferably, after the high-strength, high-definition, and light-transmitting nano-ceramic glass is subjected to secondary chemical strengthening, the high-strength, high-definition, and light-transmitting lithium yttrium aluminate nano-ceramic glass obtained in Preparation Example 6 is tested: the Mohs hardness reaches 8.0, and the fracture toughness is 10-15MPam 1 / 2 , ring-on-ring strength: 3200Mpa-5600Mpa after strengthening (glass plate thickness 0.4-0.6mm), ball drop performance: ball drop height ≥60cm; sandpaper drop height performance: standard sandpaper puncture strength ≥100cm, light transmittance 91%-96%, no yellowing, no bluish, no haziness, with high clarity and light transmittance.

[0092] Example 2

[0093] To manufacture high-strength, high-definition, and light-transmittance (nano) nano-crystalline glass, firstly, the required synthetic raw materials must be prepared according to Example 1, including synthetic aluminum-rich feldspar glass or ceramic glass materials, and then the matrix glass raw material batch is prepared according to the preparation example formula in Table 1 of Example 1, and the materials are melted, formed, microcrystal nucleated, the crystal nuclei are grown into microcrystals or nano-crystals, annealed, and strengthened to obtain high-strength, high-definition, and light-transmittance nano-crystalline glass.

[0094] Therefore, a method for preparing a high-strength, high-definition, and light-transmitting (nanometer) nano-ceramic glass in this embodiment includes:

[0095] 1. Preparation of synthetic raw materials: The synthetic raw materials in the high-strength, high-definition and light-transmittance nano-crystal glass with lithium yttrium aluminate are synthesized in a ratio to obtain the corresponding synthetic mineral material. The synthetic raw material described in this embodiment is a synthetic aluminum-rich feldspar glass or ceramic glass material, and its chemical formula is K2O / Na2O / Li2O / CaO / BaOXAl2O3YSiO2, 1.1≤X≤2.4, Y=2-6, which is expressed as one or two or more synthetic aluminum-rich feldspar, synthetic aluminum-rich sodium feldspar, synthetic aluminum-rich potassium-sodium feldspar, synthetic aluminum-rich lithium feldspar, synthetic aluminum-rich calcium feldspar, and synthetic aluminum-rich barium feldspar. Glass or composite ceramic glass materials, wherein the two or more synthetic aluminum-rich feldspar glasses or composite ceramic glass materials at least include synthetic aluminum-rich sodium feldspar glass or composite ceramic glass materials. The synthetic alumina-rich feldspar ceramic glass material is prepared according to the chemical formula K2O / Na2O / Li2O / CaO / BaOXAl2O3YSiO2, in which the weight percentages of K2O / Na2O / Li2O / CaO / BaO, Al2O3, and SiO2 are proportioned. The corresponding precursor raw materials containing K2O / Na2O / Li2O / CaO / BaO, Al2O3, and SiO2 are prepared into a batch material, which is ground through a 300-1000 mesh sieve, and the obtained dry powder is sintered and thermally synthesized at a firing temperature of 1200°C-1300°C to obtain the synthetic alumina-rich feldspar ceramic glass material, or the obtained dry powder is melted at a melting temperature of 1400°C-1500°C and then water quenched to obtain the synthetic alumina-rich feldspar glass material.

[0096] Preferably, the synthetic aluminum-rich feldspar glass or ceramic glass material is a synthetic aluminum-rich sodium potassium feldspar ((Na2O) Z ·(K2O) 1-Z·XAl2O3·YSiO2, X=2.3, Y=6 synthetic aluminum-rich sodium potassium feldspar) glass or ceramic glass material, the chemical components contained in it include by weight percentage: Na2O 8%-12%, K2O 1%-3%, Al2O320%-30%, SiO250%-60%, CaO 3%-7%, MgO 1%-3%, ZrO20.5%-5%, Sb2O30.03%-0.3%, La2O30.3%-5%, that is, on the basis of Na2O, K2O, Al2O3, SiO2 contained in synthetic aluminum-rich sodium potassium feldspar, CaO 3%-7%, MgO 1%-3%, ZrO2 0.5%-5%, Sb2O3 0.03%-0.3%, La2O3 0.3%-5%, to improve the performance of synthetic aluminum-rich sodium potassium feldspar glass or ceramic glass materials.

[0097] It is further preferred that the chemical components contained in the synthetic aluminum-rich sodium potassium feldspar glass or ceramic glass material include, by weight percentage: Na2O 10%, K2O 2%, Al2O3 25%, SiO2 54.4%, CaO 5.3%, MgO 2%, ZrO2 0.5%, Sb2O3 0.3%, La2O3 0.5%. According to the corresponding precursor raw materials containing K2O / Na2O / CaO, Al2O3 and SiO2, the corresponding potassium / sodium / calcium feldspar raw materials are used in proportion, and alumina powder equivalent to 130% of the Al2O3 content in the feldspar raw material, light-burned magnesium powder or magnesia containing MgO, zirconium oxide powder with a particle size of less than 10nm, Sb2O3 high-purity chemical powder, La2O3 high-purity chemical powder are added to make (aluminum-rich feldspar) dry powder ingredients, and the powder is crushed and ground evenly to 300-1000 The dry powder batch is obtained, and the aluminum-rich sodium potassium feldspar ceramic glass material is synthesized by calcining or the obtained dry powder batch is melted at a melting temperature of 1400℃-1500℃ and then quenched with water to obtain a synthetic aluminum-rich feldspar glass material; or the corresponding potassium / sodium / lithium / calcium carbonate chemical raw materials are used, that is, according to the required proportion of the corresponding raw materials containing K2O, Na2O, CaO and Al2O3 and SiO2, MgO, ZrO2, Sb2O3, La2O3 chemical components, K2 O, Na2O, CaO sources are carbonate raw materials such as potassium carbonate, sodium carbonate, calcium carbonate, alumina source is alumina powder, SiO2 source is high-purity quartz powder, MgO source is light-burned magnesium powder or magnesia, ZrO2 source is zirconium oxide powder with a particle size less than 10nm, Sb2O3 is high-purity chemical powder, La2O3 is high-purity chemical powder, the alumina powder is 300-1000 mesh alumina fine powder, the high-purity quartz powder is 1000-2000 mesh high Pure quartz ultrafine powder, potassium carbonate, sodium carbonate, calcium carbonate as 300-1000 mesh powder, 300-1000 mesh alumina powder equivalent to 130% of the Al2O3 content in the feldspar raw material, 1000-2000 mesh high purity quartz powder are prepared into ingredients, stirred evenly, and calcined and thermally synthesized to obtain the synthetic mineral raw material of the synthetic aluminum-rich sodium potassium feldspar ceramic glass material, or the obtained ingredients are melted at a melting temperature of 1400°C-1500°C and then water quenched to obtain the synthetic aluminum-rich feldspar glass material. The aluminum-rich sodium potassium feldspar (feldspar) glass material (Na2O) used in the preparation example in Table 1 Z (K2O) 1-ZXAl2O36SiO2 (X=2.3) is taken as an example: 1 weight part of refined sodium-potassium feldspar powder is added with 130% weight part of alumina powder equivalent to the amount of alumina in the sodium-potassium feldspar, and the powder is evenly ground to 600 mesh to obtain a dry powder batch material, which is calcined at 1300°C to obtain a synthetic mineral material of aluminum-rich sodium-potassium feldspar ceramic glass material, and then the aluminum-rich sodium-potassium feldspar ceramic glass material is mixed with light-burned magnesium powder or magnesia containing MgO, zirconium oxide powder with a particle size of less than 10nm, Sb2O3 high-purity chemical powder, and La2O3 high-purity chemical powder according to the chemical composition ratio: Na2O 10%, K2O 2%, Al2O3 25%, SiO2 54.4%, CaO 5.3%, MgO 2%, ZrO2 0.5%, Sb2O3 0.3%, La2O3 0.5%. The corresponding raw materials are prepared into dry powder batch, which is melted at a melting temperature of 1400°C-1500°C and then quenched with water to obtain a synthetic aluminum-rich sodium potassium feldspar glass material.

[0098] 2. Formula and ingredients: Mix the synthetic materials with other raw materials according to the formula ratio requirements;

[0099] Taking the synthetic aluminum-rich sodium potassium feldspar glass material as an example, the preferred chemical composition includes Na2O 10%, K2O 2%, Al2O3 25%, SiO2 54.4%, CaO 5.3%, MgO 2%, ZrO2 0.5%, Sb2O3 0.3%, La2O3 0.5%, and the raw material including lithium oxide, yttrium oxide, aluminum oxide, and silicon dioxide as chemical components determined by Li2O-Y2O3-Al2O3-SiO2 system glass includes the following chemical components by weight percentage: Li2O 10%-16%, Y2O32%-20%, Al2O30.5%-2%, SiO268%-86.5%, also including ZrO2 fine powder 2.5%-12%, Ga2O30%-5%, SnO21.0%-3% as a clarifier, P2O51%-5% as a nucleating agent, when taking values ​​respectively within the composition range, the synthetic aluminum-rich sodium feldspar glass material required in the formulations of each preparation example in Table 1 of this Example 1 and the raw material batch containing the chemical components of Li2O, Y2O3, Al2O3, SiO2, ZrO2, Ga2O3, SnO2, and P2O5 are obtained.

[0100] According to the raw material batch formula table of the matrix glass preparation example of the nano-microcrystalline glass in Table 1 of Example 1, the ingredients are prepared. Taking the raw material batch formula in Preparation Example 6 in Table 1 as an example, 20% of the raw materials of the aluminum-rich sodium potassium feldspar (feldspar) glass material prepared by the above synthetic raw materials, 10% of Li2O, 6.5% of Y2O3, 1% of Al2O3, 1.5% of SnO2, 49.1% of SiO2, 8.9% of ZrO2, 1% of Ga2O3, and 2% of P2O5 are prepared. Li2O is introduced from lithium carbonate Li2CO3 raw material, Y2O3 adopts high-purity chemical raw material powder, aluminum oxide Al2O3 source adopts aluminum oxide powder, SiO2 source adopts high-purity quartz powder, ZrO2 adopts high-purity chemical raw material zirconium oxide nano-powder, Ga2O3 adopts high-purity chemical raw material powder, and P2O5 is introduced from diammonium phosphate (NH4H2PO3) raw material. The alumina powder is 300-1000 mesh alumina fine powder, the high-purity quartz powder is 1000-2000 mesh high-purity quartz fine powder, and the Y2O3 high-purity chemical raw material powder and lithium carbonate Li2CO3 are 300-1000 mesh powders.

[0101] 3. Processing and mixing: The raw materials of the ingredients are crushed to the required fineness, mixed and mixed evenly to obtain a dry powder glass raw material batch; yttrium oxide Y2O3 must be crushed to nanometer level (nm), controlled within 100nm, and other raw materials used are powder materials controlled at 1000-2000 mesh, and the ingredients of the formula are subjected to pollution-free ball milling (small-particle ball milling media Φ1-2mm accounts for more than 60%), and the solid phase material is ball milled uniformly as the precursor material of the glass material of this technology (D5090%).

[0102] 4. Melting molding: Add the dry powder batch into the glass melting equipment for melting, clarification and homogenization, and use appropriate molding methods according to product requirements;

[0103] Preferably, the dry powder batch material is added into a glass melting device during the melting and forming, and the glass melting device includes two types: one is to add the dry powder batch material into a sagger for melting glass, and place the sagger in a high temperature furnace in an oxidizing atmosphere or an oxidizing-reducing atmosphere for melting, clarification and homogenization;

[0104] It is further preferred that the sagger is a magnesium aluminum spinel sagger or an α-corundum-mullite sagger or an α-corundum-quartz glass sagger.

[0105] Further preferably, the magnesia-alumina-spinel sagger is a synthetic composite magnesia-alumina-spinel sagger.

[0106] It is further preferred that the magnesia-alumina spinel sagger is a synthetic composite magnesia-alumina spinel sagger; it is further preferred to use the synthetic composite magnesia-alumina spinel sagger described in Chinese patent application No.: ZL202210579939.2, that is, a composite magnesia-alumina spinel sagger prepared by the synthesis method of Chinese patent application No.: ZL202210579939.2.

[0107] Preferably, the glass melting equipment adopts the second method: adding the dry powder batch material into the glass melting furnace to melt, clarify and homogenize;

[0108] More preferably, the melting temperature is 1550° C. to 1600° C., and the clarifying temperature is 1580° C. to 1600° C. In this embodiment, the melting temperature is 1600° C., and the clarifying temperature is 1600° C.

[0109] Preferably, the molding temperature is 1350°C to 1410°C. The molding method used in this embodiment is selected from the sagger in-situ molding method, the casting method, and the overflow method according to the product requirements. The molding temperature of this embodiment is 1400°C.

[0110] 5. Nucleation and crystallization: The formed glass products are nucleated at the nucleation temperature, and then crystallized by controlling the temperature and time to control the grain growth into microcrystals or nanocrystals of the required fineness and microcrystal amount;

[0111] Preferably, the nucleation crystallization is performed on the formed product, and the temperature of the nucleation crystallization is: nucleation at a temperature of 530°C-580°C, nucleation time: 2-4h, crystallization temperature 600°C-700°C, crystallization time: 2-4h.

[0112] According to the raw material formulation of the matrix glass preparation example of the nano-ceramic glass in Table 1 of Example 1, taking Preparation Example 6 as an example, the temperature system of the obtained matrix glass undergoing the nucleation crystallization thermodynamic treatment is as follows: the formed glass product is subjected to nucleation crystallization, and the temperature of the formed glass product is about 700°C,

[0113] (1) 700°C → 550°C, cooling rate 0.5°C / min, keeping at 550°C for 3 hours for nucleation;

[0114] (2) 550°C → 650°C, heating rate 0.5°C / min, keeping at 650°C for 4 hours for crystallization.

[0115] Preferably, after the nucleation and crystallization, nano-ceramic glass is obtained.

[0116] The nano-crystalline mineral composition of the nano-crystalline glass prepared in the preparation example in Table 1 of Example 1 includes (vol%): sodium nepheline 1%-30%, lithium yttrium aluminum silicate feldspar 20%-50%, lithium disilicate (Li2Si2O7) 30%-50%, yttrium aluminum garnet 3%-15%, spodumene (LiAl(SiO3)2) 1%-5% and other nano-crystalline mineral components; and the residual matrix glass coexists to form a nano-crystalline glass with uniform microstructure, high strength, high clarity and light transmittance;

[0117] 6. Annealing: Anneal the crystallized product to eliminate the thermal stress in the glass body to obtain high-strength, high-definition and high-transmittance nano-ceramic glass products.

[0118] Preferably, the annealing temperature is 500°C to 550°C, and the heating rate is 0.5°C-1

[0119] ℃ / min, annealing time 2-4 hours, from annealing temperature to room temperature at 0.2℃-0.5

[0120] The cooling rate is ℃ / min.

[0121] The annealing temperature system is as follows: the crystallized product is heated from room temperature to 500°C-550°C at a heating rate of 0.5°C-1.0°C / min, kept at 500°C-550°C for 2-4 hours, and annealed, and the cooling rate is 0.2°C-0.5°C / min from the annealing holding temperature to room temperature.

[0122] According to the different raw material formulations of the matrix glass preparation examples of the nano-ceramic glass in Table 1 of Example 1, the specific operation of the annealing temperature system of the obtained nano-ceramic glass is different. This embodiment still takes Preparation Example 6 as an example, and the annealing temperature system of the obtained nano-ceramic glass is: the crystallized product is annealed from room temperature to 500°C, with a heating rate of 0.5°C / min, and kept at 500°C for 4 hours; then the annealing temperature is from 500°C to room temperature at a heating rate of 0.4

[0123] The temperature is lowered at a rate of ℃ / min (this is a single annealing mode).

[0124] Preferably, before the nucleation and crystallization, the formed glass product is pre-annealed, and the process is: first, the glass product is raised from the temperature after forming to 700°C, the heat preservation time is 4h, and then the temperature is reduced to 550°C at 0.3°C / min for the pre-annealing, the pre-annealing heat preservation time is 3 hours, and then the temperature is reduced to 500°C at 0.3°C / min, the heat preservation time is 3 hours, and then the temperature is increased to the nucleation temperature of 550°C at no more than 0.5°C / min, and the subsequent nucleation and crystallization and subsequent annealing of the crystallized nano-ceramic glass are performed (this is a two-annealing mode). The subsequent annealing of the nano-ceramic glass is the same as that described in the previous annealing mode, and will not be described in detail.

[0125] It is further preferred that the annealing and nucleation crystallization adopt the in-situ growth method for the matrix glass molding using the sagger in-situ shaping method, that is, after the glass is formed directly through the shape of the sagger, the sagger together with the matrix glass in the sagger is directly placed in a crystallization furnace for nucleation crystallization and then annealed in an annealing kiln to obtain a high-definition and light-transmitting nano-ceramic glass. The mode of nucleation crystallization and annealing heat treatment can be a single annealing mode or a double annealing mode as described above. The temperature regime of the nucleation crystallization and annealing heat treatment is the same as described above.

[0126] It is further preferred that the in-situ growth method is used to obtain high-definition and light-transmitting nano-ceramic glass, the nano-ceramic glass is separated from the sagger, and further formed and processed to obtain the required structural parts, and then strengthened. For example, after the sagger is divided, the cut waste sagger material and waste glass material are recycled and reused.

[0127] Preferably, after obtaining the transparent nano-ceramic glass as above, the process further includes: further molding and processing the high-definition and light-transmitting nano-ceramic glass product to obtain the desired structure, and then performing a strengthening treatment. As described above in this embodiment, the nano-ceramic glass and the sagger are separated to obtain a glass ingot (or the glass liquid from the glass kiln is formed into a glass ingot, which is then subjected to nucleation, crystallization and annealing to obtain a high-definition and light-transmitting nano-ceramic glass ingot), and the glass ingot is then cut into glass sheets such as mobile phone panels (or back panels) with a thickness of 0.2-0.5 mm using a diamond wire cutter.

[0128] In order to further improve the strength, the nano-glass-ceramic product is subjected to a strengthening treatment, which includes physical strengthening or chemical strengthening.

[0129] Further preferably, the chemical strengthening is one-time chemical strengthening or two-time chemical strengthening, and the depth of the surface compressive stress layer generated by ion exchange after strengthening is 60-200 μm.

[0130] It is further preferred that the two chemical strengthenings are two step ion exchange strengthenings, wherein the first strengthening is Na + →Li + (Sodium ions replace lithium ions), the second strengthening is K + →Na + (potassium ions replace sodium ions), K + →Li + (Potassium ions replace lithium ions), thereby greatly improving the mechanical strength of the glass microcrystals.

[0131] It is further preferred that in the two step ion exchange enhancements:

[0132] The first strengthening is as follows: placing the nano-crystalline glass product in molten salt, wherein the molten salt is: KNO3 95wt% + NaNO3 4.8wt%-5wt% + CsNO3 0-0.2wt% plus 0.5wt% Al2O3 powder, and keeping the temperature at 460℃-480℃ for 4-6 hours.

[0133] The second strengthening is as follows: the nano-glass-ceramic product after the first strengthening is placed in molten salt again, the molten salt used is: KNO3, at 380°C, and kept warm for 2-6 hours.

[0134] Taking the high-definition and light-transmitting nano-ceramic glass of Preparation Example 6 in Table 1 of Example 1 as an example, the first chemical strengthening was carried out. The high-definition and light-transmitting nano-ceramic glass was placed in a mixed salt bath of 95wt% KNO3+4.8wt% NaNO3+0.2wt% CsNO3 (plus 0.5wt% Al2O3 powder) for strengthening ion exchange. The ion exchange temperature was 460°C and the exchange time was 4 hours. + →Li + The depth of the compressive stress layer generated by the exchange is 100μm.

[0135] The second reinforcement is K + →Na + The molten salt used is KNO3, and the ion exchange is carried out at 380℃ and kept warm for 6 hours, that is, the ion exchange time is 6 hours. + →Na + , K + →Li + The depth of the compressive stress layer generated by the exchange is 180μm.

[0136] The high-strength, high-definition, and light-transmitting nano-ceramic glass of lithium yttrium aluminate silicate of the present invention has been tested to achieve the following technical performance indicators:

[0137] Anti-drop height test: The glass piece does not break when dropped vertically from a height of 1.8-2.2 meters;

[0138] For example, a tempered glass sheet with a length and width of 5×5 cm and a thickness of 0.5 mm will not break if it falls vertically from a height of 2 meters;

[0139] Fracture toughness: 5-8MPa*m before strengthening 1 / 2 , after strengthening 10-12MPa*m 1 / 2 After strengthening, the deeper the ion exchange layer (the thicker the thickness), the higher the fracture toughness strength;

[0140] Hardness: Mohs hardness 6-7 before strengthening, Mohs hardness 7-8 after strengthening;

[0141] After ring-on-ring strengthening (glass plate thickness 0.4-0.6mm) 3200Mpa-5000Mpa;

[0142] Chemically strengthened compressive stress layer thickness: 20-120μm;

[0143] Thermal expansion coefficient: 1.5×10 -6 / ℃~7.8×10 -6 / ℃, softening point: 800~880℃(viscosity η=1.5×10 9 -3.5×10 9 Poise), annealing point: 500℃~550℃(viscosity η=1.0×10 13 ~2.5×10 13 poise), strain point: 480℃~520℃(viscosity η=1.0×10 14.5 moor);

[0144] Optical properties: 1. Refractive index: 1.56-1.6; 2. 91%< visible light transmittance ≤ 96%; 3. Haze: <0.1%;

[0145] Mechanical properties include: 1. Poisson's ratio: 0.21-0.23; 2. Young's modulus after strengthening: 11.5-14.1Mpsi; 3. Vickers hardness before strengthening ≥720kgf / mm 2 , Vickers hardness after strengthening ≥780kgf / mm 2 ; 4. The bending strength before strengthening is greater than 550MPa, and the bending strength after strengthening is greater than 850Mpa;

[0146] Nanocrystal particle size: mainly 5-40nm nanocrystals (the largest nanocrystals of the rest are less than 100nm). Figure 1The scanning electron microscope (SEM) image of the nano-ceramic glass microstructure of the present invention is magnified 200K times. From the microstructure diagram, it can be seen that the crystallinity of the nano-ceramic glass reaches 90-95% (vol%), and the size of all precipitated microcrystals is 5-40nm, which is dispersed and evenly distributed. The small spherules in the figure are evenly distributed, and each small spherule is a nano-scale crystal. The particle size of nanocrystals is about 5-40nm, and they are interconnected like a densely woven carpet, which also explains why the high-strength, high-definition and transparent nano-crystalline glass with lithium yttrium aluminosilicon has high fracture toughness; in the microstructure of this nano-crystalline glass, lithium disilicate nano-crystals are less than 50nm, and the periphery is distributed with Li2O-Y2O3Al2O3-SiO2 / Y2O3ZrO2 solid solution and nano-yttrium aluminosilicon feldspar and nano-spodumene, which are all wrapped by mother liquid glass and lithium yttrium aluminosilicon feldspar glass, similar to the organizational structure of cell walls wrapping cells: the mother liquid glass wraps the precise structure of the composite material of nano-crystalline glass with microcrystalline bionic structures such as nano-lithium disilicate and lithium yttrium aluminosilicon feldspar.

[0147] Nanocrystal types: Figure 2 The X-ray diffraction diagram of Example 6 of Table 1 of Example 1 of the nano-ceramic glass of the present invention is shown in FIG. 1. The X-ray diffraction diagram shows that the nano-crystals present in the nano-ceramic glass include (vol%): 35% lithium yttrium aluminate silicate (LiYAl(SiO3)) feldspar (the diffraction peak is not shown in the figure), 30% lithium disilicate (Li2Si2O7), 30% yttrium aluminum garnet (Y3Al5O 12 ) 8%, spodumene (LiAl(SiO3)2) 3%, sodium nepheline (diffraction peak not shown in the figure) 18%, and other nanocrystalline mineral components. The total amount of microcrystals or nanocrystals accounts for 94% of the nanocrystalline glass, and the remaining basic glass in the nanocrystalline glass is 6%. The nanocrystals and the residual matrix glass coexist to form a nanocrystalline glass with uniform microstructure, high strength, high clarity and light transmittance; lithium disilicate crystals (Li2Si2O7) and yttrium aluminum garnet (Y3Al5O 12 ) synthesized lithium yttrium aluminosilicate (LiYAl(SiO3), with SnO in the nano-ceramic glass as a mineralizer in the synthesis process) feldspar. Lithium yttrium aluminosilicate (LiYAl(SiO3)) crystals are dominant in the crystals, so that the nano-ceramic glass of the present invention is not yellow, blue or hazy, has high clarity and transmittance, and has a transmittance of 91%-96%. It also has small grains, small expansion coefficient, high thermal stability, high strength, and high toughness. The sandpaper drop height performance test: the standard 80-mesh sandpaper puncture strength is ≥100cm.

[0148] Tyndall effect test: When a beam of visible red light passes through the nano-microcrystalline glass plate perpendicular to the thickness plane, a very bright red light column can be seen on the flat surface of the glass, that is, the Tyndall effect light column crosses the flat surface of the glass, indicating that the nano-microcrystalline glass contains microcrystals with a diameter d of 1 to 100nm, and the particle size is smaller than the wavelength of the incident light (the wavelength of visible light is approximately between 360 and 700nm). Therefore, when visible light passes through the nano-microcrystalline glass body, it will produce obvious scattering. The intensity of the scattered light increases with the increase in the concentration of nano-microcrystalline particles in the dispersed system. The stronger the scattered light, the more it proves that the particle size of the nano-microcrystalline is greater than 1nm (given by Figure 1 The larger the proportion of nanocrystals (shown as 5-40nm), the more scattering occurs, and the higher the proportion of nanocrystals (90%-95%).

[0149] Example 3

[0150] This embodiment is an application of high-strength, high-definition, and light-transmitting nano-ceramic glass with lithium yttrium aluminosilicate.

[0151] The high-strength, high-definition and light-transmittance nano-microcrystalline glass with lithium yttrium aluminate silicate of the present invention is used to make mobile phone cover panels and cover back panels: due to the high surface hardness, the mobile phone panel made of the glass has good wear resistance, the surface is not easy to be scratched, does not fog or blur, the display has high-definition light transmittance, high fracture toughness, high bending strength, high light transmittance, and can be made into 3D panel glass. It can also be used to make mobile phone back panels, has no shielding properties for radio waves, is conducive to the arbitrary arrangement of mobile phone antennas in the machine, and the reception and transmission of signals are not affected by the panel and the back panel.

[0152] Used for optical glass: Due to the synergistic effect of various nano-crystals, the strength of nano-crystal glass is improved. At the same time, the refractive index of various nano-crystals is close to that of residual glass. It has high light transmittance, is not yellowish, bluish, hazy, or moldy, has high clarity, can meet the use requirements of optical glass, has high hardness and wear resistance, and is used for cameras, glasses glass, window glass and shells of high-end instruments and equipment, etc.

[0153] It can also be used for cover glass of high-end electronic products, as well as windshields and side windows of high-speed trains and aircraft, vehicle control screens, and quantum radar panels.

Claims

1. A high-strength, high-definition, and light-transmitting nano-ceramic glass with lithium yttrium aluminate silicate, characterized in that: The high-strength, high-definition and light-transmitting nano-crystalline glass with lithium yttrium aluminate silicate is obtained by melting and crystallizing raw materials including synthetic aluminum-rich feldspar glass or ceramic glass materials, lithium oxide, yttrium oxide, aluminum oxide and silicon dioxide determined by Li2O-Y2O3-Al2O3-SiO2 system glass, and zirconium oxide micropowder.

2. The high-strength, high-definition, and light-transmitting nano-ceramic glass with lithium yttrium aluminate silicate according to claim 1, characterized in that: The chemical formula of the synthetic aluminum-rich feldspar glass or ceramic glass material is K2O / Na2O / Li2O / CaO / BaOXAl2O3YSiO2, 1.1≤X≤2.4, Y=2-6, which is represented by a glass or composite ceramic glass material of one or two or more of synthetic aluminum-rich potassium feldspar, synthetic aluminum-rich sodium feldspar, synthetic aluminum-rich sodium potassium feldspar, synthetic aluminum-rich lithium feldspar, synthetic aluminum-rich calcium feldspar, and synthetic aluminum-rich barium feldspar. Among them, the two or more kinds of synthetic aluminum-rich feldspar glass or composite ceramic glass materials at least include synthetic aluminum-rich sodium feldspar glass or composite ceramic glass material.

3. The high-strength, high-definition, and light-transmitting nano-ceramic glass with lithium yttrium aluminosilicate according to claim 1, characterized in that: The raw materials include by weight percentage: The synthetic aluminum-rich feldspar glass or ceramic glass material is 1%-30%, The Li2O-Y2O3-Al2O3-SiO2 system glass contains 65% to 90% of the raw materials of lithium oxide, yttrium oxide, aluminum oxide and silicon dioxide as chemical components. The zirconium oxide powder is 2.5%-12%, Nucleating agent 1%-5%, Clarifying agent 0.5%-3%, Also includes gallium oxide 0%-5%, Obtain batch materials for molten glass.

4. The high-strength, high-definition, and light-transmitting nano-ceramic glass-ceramic having lithium yttrium aluminosilicate according to claim 1, characterized in that: The raw materials of the Li2O-Y2O3-Al2O3-SiO2 system glass, which are lithium oxide, yttrium oxide, aluminum oxide and silicon dioxide as chemical components, include the following chemical components by weight: Li2O 10%-16%, Y2O3 2%-20%, Al2O3 0.5%-8%, SiO2 68%-86.5%, SnO2 1.0%-3% as a clarifier, and P2O5 1%-5% as a crystal nucleating agent.

5. The high-strength, high-definition, and light-transmitting nano-ceramic glass with lithium yttrium aluminosilicate according to claim 2, characterized in that: The synthetic aluminum-rich feldspar glass or ceramic glass material is a synthetic aluminum-rich sodium-potassium feldspar glass or ceramic glass material, and the chemical components contained therein include, by weight percentage: Na2O 8%-12%, K2O 1%-3%, Al2O3 20%-30%, SiO250%-60%, CaO 3%-7%, MgO 1%-3%, ZrO2 0.5%-5%, Sb2O3 0.03%-0.3%, and La2O3 0.3%-5%.

6. The high-strength, high-definition, and light-transmitting nano-ceramic glass with lithium yttrium aluminosilicate according to claim 4, characterized in that: The Y2O3 and the ZrO2 are synthesized into yttria-stabilized zirconia solid solution during the melting and crystallization process. The particle size of the yttria raw material is less than 100nm, and the other raw materials are powder materials with a particle size of 1000-2000 mesh, thereby obtaining nano-ceramic glass.

7. The high-strength, high-definition, and light-transmitting nano-ceramic glass-ceramic having lithium yttrium aluminosilicate according to claim 6, characterized in that: The raw material formula of the nano-microcrystalline glass includes SnO2, and SnO2 is used as a solvent to synthesize yttria-stabilized zirconia solid solution with nano-Y2O3 and ZrO2 during the melting and crystallization process, so that the weight percentage of ZrO2 dissolved in Y2O3 in the nano-microcrystalline glass is in the range of 0.5%-12% to synthesize yttria-stabilized zirconia solid solution nano-microcrystals without producing milky white microcrystals.

8. The high-strength, high-definition, and light-transmitting nano-ceramic glass-ceramic having lithium yttrium aluminosilicate according to claim 6, characterized in that: The microcrystalline phases precipitated in the nano-microcrystalline glass include, by volume percentage: 1%-30% sodium nepheline, 20%-50% lithium yttrium aluminum silicate feldspar, 30%-50% lithium disilicate, 3%-15% yttrium aluminum garnet, 1%-5% spodumene, and nano-microcrystalline accounts for 90%-95% of the total nano-microcrystalline glass.

9. The high-strength, high-definition, and light-transmitting nano-ceramic glass-ceramic having lithium yttrium aluminosilicate according to claim 8, characterized in that: The nanocrystals have grains smaller than 50 nm.

10. The high-strength, high-definition, and light-transmitting nano-ceramic glass-ceramic having lithium yttrium aluminosilicate according to claim 8, characterized in that: The chemical composition of the basic glass after microcrystal precipitation is as follows: Al2O3 2%-3.7%, Y2O3 2%-10%, Li2O 10%-16%, Na2O 1%-2%, K2O 0.2%-0.6%, SnO 0.5%-3%, Sb2O3 0.3%-0.5%, SiO2 58.9%-82.3%, La2O3 0.1%-2% ZrO2 2.5%-12%, P2O5 1%-5%.

11. A method for preparing high-strength, high-definition and high-transmittance nano-ceramic glass with lithium yttrium aluminate silicate, comprising: Preparation of synthetic raw materials: synthesizing the synthetic raw materials in the high-strength, high-definition and light-transmittance nano-ceramic glass with lithium yttrium aluminate silicate according to any one of claims 1 to 10 according to a proportion to obtain the corresponding synthetic mineral material; Formula batching: Compound the synthetic material with other raw materials according to the formula ratio requirements; Processing and mixing: crush the raw materials of the ingredients to the required fineness, mix and mix evenly to obtain dry powder glass raw batch; Melting molding: Add the dry powder batch into the glass melting equipment for melting, clarification and homogenization, and use appropriate molding methods according to product requirements; Nucleation and crystallization: The formed glass products are nucleated at the nucleation temperature, and then crystallized by controlling the temperature and time to control the grain growth into microcrystals or nanocrystals of the required fineness and microcrystal quantity; Annealing: Anneal the crystallized product to eliminate the thermal stress in the glass body to obtain high-strength, high-definition and light-transmitting nano-ceramic glass products.

12. The method for preparing high-strength, high-definition and light-transmittance nano-ceramic glass with lithium yttrium aluminosilicate according to claim 11, characterized in that: Also includes: After the nano-glass-ceramic product is further molded and processed to obtain the desired structure, it is subjected to strengthening treatment.

13. The method for preparing high-strength, high-definition and light-transmitting nano-ceramic glass with lithium yttrium aluminosilicate according to claim 12, characterized in that: The strengthening of the nano-ceramic glass product includes physical strengthening or chemical strengthening.

14. The method for preparing high-strength, high-definition and high-transmittance nano-ceramic glass with lithium yttrium aluminosilicate according to claim 13, characterized in that: The chemical strengthening is one-time chemical strengthening or two-time chemical strengthening. The depth of the surface compressive stress layer generated by ion exchange after strengthening the nano-ceramic glass product is 60-200 μm.

15. The method for preparing high-strength, high-definition and high-transmittance nano-ceramic glass with lithium yttrium aluminosilicate according to claim 14, characterized in that: The two chemical strengthenings are two step ion exchange strengthenings, and the first strengthening is Na + →Li + , the second reinforcement is K + →Na + , K + →Li + .

16. The method for preparing high-strength, high-definition and high-transmittance nano-ceramic glass with lithium yttrium aluminosilicate according to claim 15, characterized in that: The first strengthening step is to place the nano-ceramic glass product in molten salt, wherein the molten salt is: KNO3 95% + NaNO3 4.8%-5% + CsNO3 0-0.2%, and 0.5% Al2O3 powder is added, and the temperature is kept at 460℃-480℃ for 4-6 hours; The second strengthening is as follows: the nano-ceramic glass product after the first strengthening is placed in molten salt again, the molten salt used is KNO3, and the temperature is kept at 380℃ KNO3 molten salt for 2-6 hours.

17. The method for preparing high-strength, high-definition and high-transmittance nano-ceramic glass with lithium yttrium aluminosilicate according to claim 11, characterized in that: In the melting molding, the dry powder batch material is added into the glass melting equipment, that is, the dry powder batch material is added into the sagger for melting glass, and the sagger is placed in a high-temperature furnace in an oxidizing atmosphere or an oxidizing-reducing atmosphere for melting, clarification and homogenization.

18. The method for preparing high-strength, high-definition and high-transmittance nano-ceramic glass with lithium yttrium aluminosilicate according to claim 17, characterized in that: The sagger is a magnesium aluminum spinel sagger or an α-corundum-mullite sagger or an α-corundum-quartz glass sagger.

19. The method for preparing high-strength, high-definition and high-transmittance nano-ceramic glass with lithium yttrium aluminosilicate according to claim 18, characterized in that: The magnesia-alumina-spinel sagger is a synthetic composite magnesia-alumina-spinel sagger.

20. The method for preparing high-strength, high-definition and light-transmitting nano-ceramic glass with lithium yttrium aluminosilicate according to claim 11, characterized in that: The nucleation crystallization adopts an in-situ growth method, that is, the glass is formed directly by in-situ shaping of the sagger, and the sagger together with the glass in the sagger is directly nucleated and crystallized in a kiln and then annealed to obtain high-definition and light-transmitting nano-ceramic glass.

21. The method for preparing high-strength, high-definition and light-transmitting nano-ceramic glass with lithium yttrium aluminosilicate according to claim 20, characterized in that: The nano-ceramic glass obtained by the in-situ growth method nucleation and crystallization is separated from the sagger, and further formed and processed to obtain the required structural parts, and then strengthened.

22. The method for preparing high-strength, high-definition, and light-transmitting nano-ceramic glass with lithium yttrium aluminosilicate according to claim 11, characterized in that: In the melt forming, the dry powder batch material is added into a glass melting furnace for melting, clarification and homogenization, and the forming is carried out by using a casting method, a calendering method or an overflow method.

23. The method for preparing high-strength, high-definition and light-transmittance nano-ceramic glass with lithium yttrium aluminosilicate according to claim 22, characterized in that: The melting temperature is 1550°C to 1600°C, the clarifying temperature is 1580°C to 1600°C, and the molding temperature is 1350°C to 1410°C.

24. The method for preparing high-strength, high-definition and light-transmitting nano-ceramic glass with lithium yttrium aluminosilicate according to claim 11, characterized in that: The nucleation crystallization is to perform nucleation crystallization on the formed product. The temperature of the nucleation crystallization is: nucleation at a temperature of 530°C-580°C, nucleation time: 2-4h, crystallization temperature 600°C-650°C, crystallization time: 2-4h.

25. The method for preparing high-strength, high-definition and light-transmitting nano-ceramic glass with lithium yttrium aluminosilicate according to claim 11, characterized in that: The annealing temperature is as follows: the crystallized product is heated from room temperature to 500°C to 550°C, the heating rate is 0.5°C to 1°C / min, the annealing holding time is 2-4 hours, and the cooling rate from the annealing holding temperature to room temperature is 0.2°C to 0.4°C / min.

26. The method for preparing high-strength, high-definition, and light-transmitting nano-ceramic glass with lithium yttrium aluminosilicate according to claim 24, characterized in that: Before the nucleation and crystallization, the formed glass product is pre-annealed, and the process is as follows: First, the temperature of the glass product after forming is raised to 650°C-750°C, and the holding time is 2-5 hours. Then, the temperature is lowered to 530°C-580°C at 0.2°C-0.3°C / min for the pre-annealing. The pre-annealing holding time is 2-3 hours. Then, the temperature is lowered to 500°C at 0.2°C-0.3°C / min for 2-3 hours. Then, the temperature is raised to the nucleation temperature at a rate not greater than 0.5°C / min, and the subsequent nucleation, crystallization and annealing are carried out.

27. Application of high-strength, high-definition, and light-transmitting nano-ceramic glass with lithium yttrium aluminate silicate, characterized in that: The high-strength, high-definition and light-transmittance nano-crystalline glass with lithium yttrium silicate as described in any one of claims 1 to 10 is used to make various optical glasses, including mobile phone cover panels and back panels, cameras, cover glass for high-end electronic products, and high-speed trains, aircraft windshields and side window glass, high-end instrumentation equipment window glass and housing, vehicle-mounted control screens, and quantum radar panels.

Citation Information

Patent Citations

  • A synthetic composite spinel sagger and its manufacturing method

    CN114907110B